‘I’m meant to be the success story, and I can’t be failing’: Exploring the Complicated Peer Worker Identity in the Context of the NHS in England - Watson, Emma (Journal of Recovery in Mental Health, 2025)
Background: Peer support is becoming a common feature of mental health service provision. In England most NHS mental health services now employ peer support workers (PSWs). Little is known about how the institutional context in which PSWs operate shapes their roles and identities.Aim: To develop an understanding of PSWs’ perceptions of their identity in the context of an NHS mental health service.Methods: Eighteen NHS PSWs were interviewed, and their transcripts were studied repeatedly during in-depth thematic analysis resulting in 5 themes.Results: Four of the resulting themes related to different peer worker identities (empowered survivor, not peer enough, flaky and unstable & tokenistic). The fifth related to how PSWs resist and manage the identities available to them within an institutional context. The institutional context of NHS mental health services complicates the PSW identity because of its medical construction of lived experience, as well as its dominant cost-saving agenda.Conclusions: The study furthers the understanding of how the medical, hierarchical, financially scarce context of mental health services impact PSWs’ perceptions of their identity, which is an under-explored area of research. A shift in focus away from PSWs, and onto the context that they are employed within is called for.